2019
DOI: 10.1371/journal.pone.0211416
|View full text |Cite
|
Sign up to set email alerts
|

Unlearning implicit social biases during sleep: A failure to replicate

Abstract: A 2015 article in Science (Hu et al.) proposed a new way to reduce implicit racial and gender biases during sleep. The method built on an existing counter-stereotype training procedure, using targeted memory reactivation to strengthen counter-stereotype memory by playing cues associated with the training during a 90min nap. If effective, this procedure would have potential real-world usefulness in reducing implicit biases and their myriad effects. We replicated this procedure on a sample of n = 31 college stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…While meta‐analytical evidence of TMR convincingly suggests that memories can be selectively targeted and improved during SWS, the effect sizes of individual studies vary significantly (Hu et al, 2020). In the context of bias reduction, two studies were published, both conducted using a within‐subject manipulation and auditory TMR during an afternoon nap, with the first reporting a significant TMR effect and the second reporting a null effect (Hu, Antony et al, 2015; Humiston & Wamsley, 2019). One possible explanation for this divergence in effect size across studies would emphasize the small size of an underlying effect, such that real effects are sometimes missed when small sample sizes are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While meta‐analytical evidence of TMR convincingly suggests that memories can be selectively targeted and improved during SWS, the effect sizes of individual studies vary significantly (Hu et al, 2020). In the context of bias reduction, two studies were published, both conducted using a within‐subject manipulation and auditory TMR during an afternoon nap, with the first reporting a significant TMR effect and the second reporting a null effect (Hu, Antony et al, 2015; Humiston & Wamsley, 2019). One possible explanation for this divergence in effect size across studies would emphasize the small size of an underlying effect, such that real effects are sometimes missed when small sample sizes are used.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was also ample heterogeneity of effect sizes across studies and the effect size tends to be small‐to‐moderate. With respect to TMR for social bias, only two studies have been published to date, our initial study (Hu, Antony et al, 2015) and one replication study where TMR benefits were not observed (Humiston & Wamsley, 2019). On the one hand, a divergence in TMR effect size between these two studies is unclear at present.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true given that neither object-location 13 nor emotional 26 memory seems to benefit from the manipulation even a week later. One-week-later effects of TMR have been reported for implicit biases 27 , but this failed to replicate 28 . Our prior work showed behavioural effects of TMR 10 days post-manipulation but not 6 weeks later 11 .…”
Section: Tmr Benefits Procedural Memories Up To 20 Days Post-manipulationmentioning
confidence: 92%
“…The non‐REM type dreams might occur on a daily basis (except on the days when their sleep is disturbed, Gravett et al, ), but the REM type dreams might occur only every third or fourth day when the elephants take the opportunity to lie down to sleep, indicating muscle atonia associated with REM sleep. This potentially irregular occurrence of REM sleep, and the absence of any clear form of REM sleep in cetaceans (see above), provide an important phylogenetic counter‐argument to the hypothesized association between REM sleep and memory consolidation (Ackermann, Hartmann, Papassotiropoulos, de Quervain, & Rasch, ; Boyce, Glasgow, Williams, & Adamantidis, ; Humiston & Wamsley, , ; Magidov et al, ; Rasch, Pommer, Diekelmann, & Born, ; Siegel, ; Stickgold, ; Tilley & Empson, ; Wyatt, Fram, Kupfer, & Snyder, ).…”
Section: Dreams and Other Mammals That Show Atypical Sleep Patternsmentioning
confidence: 99%